Secondary School Choice – What Do Parents Concern? - Krishnapillai, Gengeswari; Ying, Kwok See; Li Xin, Pinky Cheong; Kit, Cheong Ka; Zhen, Lee Ying; Yeau, Liew Zhun (International Business Education Journal, 2016)
There has been an increase in the students‟ enrolment to the private schools across Malaysia. The shift in the parents‟ preference on the selection of secondary school has been predominantly attributed to the dissatisfaction with the current school education system. Subsequently, this study attempts to study the factors that affect parents‟ preferences in selecting the secondary school for their children. Four factors namely school characteristics, school environment, social influences and the parents-administration-teachers (PAT) relationship that are related to school choice were examined in this study. 203 representative elements were drawn using judgmental sampling technique and structural equation modelling (SEM) analysis was used to analyse the data collected. The findings showed that all factors significantly affect the parents‟ preferences in selecting the secondary school for their children. Comparatively, the effect of school environment on the parents‟ preferences was found slightly lower than social influences, school characteristics, and PAT relationship. This study accordingly puts forward several implications for both academics and practitioners alongside recommendations for future researchers.